2019
DOI: 10.1038/s41591-019-0567-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensory feedback restoration in leg amputees improves walking speed, metabolic cost and phantom pain

Abstract: Conventional leg prostheses do not convey sensory information about motion or interaction with the ground to aboveknee amputees, thereby reducing confidence and walking speed in the users that is associated with high mental and physical fatigue 1-4 . The lack of physiological feedback from the remaining extremity to the brain also contributes to the generation of phantom limb pain from the missing leg 5,6 . To determine whether neural sensory feedback restoration addresses these issues, we conducted a study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
264
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(270 citation statements)
references
References 56 publications
5
264
1
Order By: Relevance
“…Only six studies presented detailed characteristics about the prosthetic components (i.e., prosthetic joint, foot, and socket) utilized to evaluate BFB [34,59,[78][79][80][81]. During BFB testing, most of the participants wore their prescribed prosthesis (i.e., passive mechanical or microprocessor- Table 4 depicts the results of the criteria applied to assess the quality of the reviewed articles.…”
Section: Key Data Extracted From Reviewed Articlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Only six studies presented detailed characteristics about the prosthetic components (i.e., prosthetic joint, foot, and socket) utilized to evaluate BFB [34,59,[78][79][80][81]. During BFB testing, most of the participants wore their prescribed prosthesis (i.e., passive mechanical or microprocessor- Table 4 depicts the results of the criteria applied to assess the quality of the reviewed articles.…”
Section: Key Data Extracted From Reviewed Articlesmentioning
confidence: 99%
“…During BFB testing, most of the participants wore their prescribed prosthesis (i.e., passive mechanical or microprocessor-controlled knee prostheses). In terms of BFB effectiveness and prosthetic components, the results showed that BFB systems were capable of improving the gait performance of individuals with LLA, regardless of the type of prosthetic components (i.e., passive mechanical knee or microprocessor-controlled knee or powered knee prostheses) [35,59,[79][80][81][82]. FSRs (force sensitive resistors) sensors that were attached to the plantar surface of the prosthetic foot were the most frequently used transducer for measuring the targeted gait parameters.…”
Section: Key Data Extracted From Reviewed Articlesmentioning
confidence: 99%
See 3 more Smart Citations